Robotic Confucius Disturbs, Provokes. (Asia Pacific Arts, 2012)
The article presents information on the "Breathing" sculpture of philosopher Confucius, created by artist Zhang Huan and displayed at an exhibition at the Rockbund Art Museum in Shanghai, China.